Answer :

Given P(A)=2 P(B)

P(B)=2 P(C)


P(A)=2(2P(C))


=4P(C)


By definition we know,


P(A) +P(B)+ P(C)=1


4P(C) + 2P(C) +P(C) =1


7P(C)=1


P(C)=


Therefore P(A) = 4 P(C)




P(A loses)



Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

State True or FalMathematics - Exemplar

Fill in theMathematics - Exemplar

A speaks truth inMathematics - Board Papers

Often it is takenMathematics - Board Papers

Assume that each Mathematics - Board Papers

A bag X contains Mathematics - Board Papers